2014
DOI: 10.4103/1673-5374.133137
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of ginsenoside Rb1 on hippocampal neuronal injury and neurite outgrowth

Abstract: Ginsenoside Rb1 has been reported to exert anti-aging and anti-neurodegenerative effects. In the present study, we investigate whether ginsenoside Rb1 is involved in neurite outgrowth and neuroprotection against damage induced by amyloid beta (25–35) in cultured hippocampal neurons, and explore the underlying mechanisms. Ginsenoside Rb1 significantly increased neurite outgrowth in hippocampal neurons, and increased the expression of phosphorylated-Akt and phosphorylated extracellular signal-regulated kinase 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…A large number of previous studies have shown the stimulating effects of ERK1/2 and natural products from plants on neurite outgrowth [ 56 , 57 , 58 , 59 , 60 ]. It has been reported that ginsenoside Rg1 and Rb1, and triterpenoid saponins, enhance the neurite outgrowth of hippocampal neurons by activating the ERK1/2 and PI3K/Akt pathways [ 56 , 57 ]. Ginsenoside Rd treatment also promotes the neurite outgrowth of PC12 cells by activating the MAPK/ERK and PI3K/Akt signaling proteins [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of previous studies have shown the stimulating effects of ERK1/2 and natural products from plants on neurite outgrowth [ 56 , 57 , 58 , 59 , 60 ]. It has been reported that ginsenoside Rg1 and Rb1, and triterpenoid saponins, enhance the neurite outgrowth of hippocampal neurons by activating the ERK1/2 and PI3K/Akt pathways [ 56 , 57 ]. Ginsenoside Rd treatment also promotes the neurite outgrowth of PC12 cells by activating the MAPK/ERK and PI3K/Akt signaling proteins [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…. 人参皂苷Rb1属于20(S)-原人参二醇型皂苷, 具有 促进神经系统的生长、增加生长促进激酶(Akt和ki-nase1/2)的表达、抵抗Aβ诱导的细胞凋亡等神经保护 活性 [72,73] . Rb1可用于治疗包括AD在内的与Tau蛋白相…”
Section: 他克林(Ic 50 =167 Nm)是1993年批准的第一个用于unclassified
“…It can reduce neuronal death induced by hypoxic–ischemic insults, an effect probably mediated by the activation of glucocorticoid receptors, and by the inhibition of calcium influx through NMDA receptors and L-type voltage-dependent Ca 2+ channels and the resultant reduction of intracellular free Ca 2+ [ 279 ]. It also enhances neurite outgrowth and protects against neurotoxicity induced by A β through a mechanism involving Akt and ERK 1/2 signaling [ 280 ]. This compound ( 41 ) is also shown to be capable of helping Schwann cells recover from the oxidative insult induced by H 2 O 2 .…”
Section: Classical Examples Of Neuroprotective Drugs Of Plant-origmentioning
confidence: 99%
“…Furthermore, it increases the mRNA levels, protein levels, and secretion of nerve growth factor and brain-derived neurotrophic factor in Schwann cells after incubation with H 2 O 2 [ 281 ]. Ginsenoside Rg1 ( 41 ) as well as 38 and others have been shown to reduce the amount of A β detected in the brains of animals after single oral doses [ 280 ]. Review articles on the effects of ginseng extracts and isolated ginsenosides along with the aglycones relevant to cognition in humans are also available [ 282 , 283 ].…”
Section: Classical Examples Of Neuroprotective Drugs Of Plant-origmentioning
confidence: 99%